Nitric oxide and beta-adrenergic stimulation are major regulators of preprandial and postprandial subcutaneous adipose tissue blood flow in humans. - Ardilouze, J; Fielding, B; Currie, J; Frayn, K; Karpe, F (2004)
BACKGROUND: Blood flow mediates the metabolic and endocrine roles of adipose tissue. We have previously shown that the postprandial adipose tissue blood flow (ATBF) increase is dependent on insulin sensitivity. However, subcutaneous local insulin delivery had no demonstrable effect on either preprandial or postprandial ATBF. We hypothesized that insulin may act indirectly via sympathetic activation, mainly in the postprandial period, and that nitric oxide may be an overall major regulator of subcutaneous ATBF. METHODS AND RESULTS: We investigated the endogenous preprandial and postprandial regulation of ATBF by applying local tissue blockade of beta-adrenergic (propranolol), alpha-adrenergic (phentolamine and yohimbine), and nitric oxide (NG-monomethyl-L-arginine, L-NMMA) regulation of blood flow. Healthy subjects (body mass index, 18 to 31 kg/m2) were challenged with 75 g glucose for endogenous stimulation of ATBF. We used the novel "microinfusion" technique, which allows for simultaneous local delivery of pharmacological agents (or contralateral saline) and measurement of ATBF with the 133Xe washout method. Compared with control, the preprandial ATBF was not affected by propranolol but was increased by 21% (P<0.013) and 15% (P=0.004) with phentolamine and yohimbine, respectively. A decrease of 42% (2.97+/-0.33 versus 4.75+/-0.47 mL x min(-1) x 100 g tissue(-1), P<0.01) was seen with L-NMMA. The postprandial response was blunted by 58% (0.81+/-0.42 versus 1.90+/-0.44 mL x min(-1) x 100 g tissue(-1), P<0.004) with propranolol, but neither phentolamine, yohimbine, or L-NMMA altered this response. CONCLUSIONS: Nitric oxide seems to determine the absolute level of ATBF, whereas a major proportion of the postprandial enhancement of ATBF is under beta-adrenergic regulation in vivo in humans.